Characterizing soundscapes from four reefs in the West Philippine Sea, Philippines - Alatraca, Sibyl Hanedzo D. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
Visual monitoring has been used for years to gain information and assess the health of coral reefs, but it is costly and time-consuming. Recently, researchers utilized underwater acoustics as an alternative. Despite these innovations, coral reef soundscapes have never been characterized in the Philippines. Moreover, because studies on coral reefs in the country are few and mostly limited nearshore, not much is known about offshore coral reefs. This study aimed to characterize soundscapes from four reefs in the West Philippine Sea (WPS), namely: Sabina and Ayungin Shoals, and Pagasa Island, which are offshore reefs, and Quezon in mainland Palawan. An autonomous underwater acoustic recorder was deployed at depths of up to 10 m over time periods ranging from 7:30 AM to 6:00 PM. Low and high-frequency (50-1500 Hz & 2000-20000 Hz) spectrograms were constructed to visualize and investigate variations in the <2-hr and 24-hr soundscape recordings. Acoustic complexity index (ACI) and acoustic entropy index (H) were used to evaluate the acoustic diversity between sites. The Soundscape Viewer was used to investigate diel patterns of 24-hr recordings. Results showed that snapping sounds were prevalent across all sites. Diel patterns in the two shoals showed (1) no variation in the soundscapes during daytime and that (2) biological sounds increased from dusk until dawn. The reef sites displayed similar patterns of acoustic diversity, except for Pagasa, which had the highest index values despite the presence of anthropogenic noise. Based on manual inspection, this is likely due to the variety of vocalizations rather than the effect of vessel noise. This study is the first to provide knowledge on coral reefs (especially offshore reefs) in the WPS using soundscape. This study can also serve as reference for future researchers and government initiatives in formulating conservation strategies to protect the coral reef ecosystems in the WPS.